Pengaruh Jus Belimbing dan Jus Jambu Biji Merah terhadap Penyerapan Tablet Fe Pada Ibu Hamil yang Mengalami Anemia di Klinik Ar Rahman Baros - Pinasti, Neng Fira Ayu; Azizah, Imroatul (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Anemia in pregnant women is one of the complications of pregnancy that risks increasing maternal and infant mortality. One of the efforts to overcome anemia is by giving Fe tablets, but the absorption of iron from these tablets is often disrupted due to lack of vitamin C intake. Starfruit juice and red guava juice are known to be rich in vitamin C which can increase iron absorption, thus becoming an alternative support for anemia therapy. This study is to determine the effect of star fruit juice and red guava juice consumption on the absorption of Fe tablets in anemic pregnant women at Ar Rahman Baros Clinic. This study used a quasi-experimental design with a pretest-posttest approach. The sample consisted of 20 pregnant women with anemia who were divided into intervention group (star fruit juice and red guava juice) and control group (no juice). The results of the paired sample t test statistical test in the control group obtained Pvalue = 0.115> 0.05 and in the experimental group obtained Pvalue = 0.004> 0.05 The results of statistical tests in the control and experimental groups obtained Pvalue = 0.030 < 0.05 (there is an effect of giving star fruit juice and red guava juice on the absorption of Fe tablets). Consumption of star fruit juice and red guava juice proved effective in increasing iron absorption from Fe tablets in anemic pregnant women. It is recommended to increase education and promotion of local fruit consumption rich in vitamin C as a support for anemia therapy. Keywords: Anemia, Fe Tablet, Starfruit Juice, Red Guava Juice  ABSTRAK Anemia pada ibu hamil merupakan salah satu komplikasi kehamilan yang berisiko meningkatkan angka kematian ibu dan bayi. Salah satu upaya untuk mengatasi anemia adalah dengan pemberian tablet Fe, namun penyerapan zat besi dari tablet ini sering terganggu akibat kurangnya asupan vitamin C. Jus belimbing dan jus jambu biji merah diketahui kaya akan vitamin C yang dapat meningkatkan penyerapan zat besi, sehingga menjadi alternatif pendukung terapi anemia.  Penelitian ini untuk mengetahui pengaruh konsumsi jus belimbing dan jus jambu biji merah terhadap penyerapan tablet Fe pada ibu hamil yang mengalami anemia di Klinik Ar Rahman Baros. Penelitian ini menggunakan desain kuasi-eksperimen dengan pendekatan pretest-posttest. Sampel terdiri dari 20 ibu hamil dengan anemia yang dibagi menjadi kelompok intervensi (jus belimbing dan jus jambu biji merah) dan kelompok kontrol (tanpa jus).  Hasil uji statistik paired sample t test pada kelompok kontrol didapatkan Pvalue = 0.115 > 0.05 dan pada kelompok eksperimen didapatkan Pvalue = 0.004 > 0.05 Hasil uji statistik pada kelompok kontrol dan eksperimen didapatkan Pvalue = 0.030 < 0.05 (ada pengaruh pemberian jus belimbing dan jus jambu biji merah terhadap penyerapan tablet Fe). Konsumsi jus belimbing dan jus jambu biji merah terbukti efektif dalam meningkatkan penyerapan zat besi dari tablet Fe pada ibu hamil anemia. Disarankan untuk meningkatkan edukasi dan promosi konsumsi buah lokal yang kaya vitamin C sebagai pendukung terapi anemia. Kata Kunci: Anemia, Tablet Fe, Jus Belimbing, Jus Jambu Biji Merah